Pengaruh Kualitas Pelayanan, Promosi, dan Persepsi Harga Terhadap Kepuasan Pelanggan di Restoran All You Can Eat - Tata Ardiningrum; Prawoto Prawoto (CV. ULIL ALBAB CORP, 2023)
Currently, All You Can Eat restaurants have become very popular in Indonesia. Restaurants with unlimited food systems have become popular commodities in Indonesia. Although previously less popular, recently many restaurants have adopted the concept of All You Can Eat. Research shows that especially among young people, especially women, feel more satisfied when dining at All You Can Eat restaurants. Along with the increasing number of All You Can Eat restaurants from year to year, this business has also experienced significant growth. Each All You Can Eat restaurant certainly has expertise in managing its business with various attractive concepts for customers. The aim of this research is to enhance customer satisfaction in All You Can Eat restaurants with a focus on service quality, promotion, and price perception. This research utilizes IBM Statistics Version 25 and gathers a sample of 100 customers. The research results show that customer satisfaction is positively influenced by service quality, promotion, and price perception. These three factors together have a significant and meaningful impact on customer satisfaction. Therefore, the objective of this research is to enhance service quality and promotional efforts in All You Can Eat restaurants in order to better meet consumer needs and improve customer satisfaction